Cognitive behavioral approaches for counselors - Shea, Diane (Theories for counselors series, 2016)
REBT/CBT therapies are presented with an emphasis on the therapeutic relationship from a common factors perspective. -- REBT/CBT therapies are presented with an emphasis on the therapeutic relationship from a common factors perspective. -- Research demonstrating that REBT/CBT is highly compatible with major world religions such as Christianity, Judaism, and Islam is imparted. -- The author shows that as "third wave" cognitive therapies-such as Mindfulness-Based CBT, Dialectical Behavioral Therapy, and Acceptance and Commitment Therapy-evolved, these approaches incorporated elements of spirituality into treatments while continuing to emphasize the therapeutic alliance